Investigate the importance of mechanical properties of SWCNT on doxorubicin anti-cancer drug adsorption for medical application: A molecular dynamic study - Karimzadeh, Sina; Safaei, Babak; Jen, Tien-Chien (Elsevier Science Inc, 2020)
[Abstract Not Available]
Keywords: Carbon nanotube; Doxorubicin; Drug delivery system; Molecular dynamic simulations; Density functional theory; Natural bond orbital